Divergence of Fecal Microbiota and Their Associations With Host Phylogeny in Cervinae - Li, Jiaying; Zhan, Songping; Liu, Xuanzhen; Lin, Qiang; Jiang, Jianping; Li, Xiangzhen (Frontiers in Microbiology, 2018)
Gastrointestinal microbiota, influenced by multiple factors (i.e. host phylogeny, diet and environment), may shape the adaptation of their hosts to different habitats and lifestyles, as well as the evolutionary diversification. Questions have been revealed in previous studies that if gastrointestinal microbiota divergences are in good congruence with the phylogenetic relationships of their hosts. Here, we analyzed compositions of the fecal microbiota of seven Cervinae species in the Chengdu Zoo. All sampled animals have been kept in the same environmental condition and fed identical fodder for years. Firmicutes and Bacteroidetes were dominant in their fecal microbiota. Even though some bacteria (i.e. Ruminococcaceae) were found to be common in the feces of all investigated species, some genera (i.e. Sharpea and Succinivibrio) were only examined in animals with particular digestive system. As for the intraspecies variations of microbial communities, only a few operational taxonomic units (OTUs) were shared among replicates of the same host species, however, they accounted for most of the sequences. Correlation between the fecal microbiota divergence and host phylogeny was observed, but they were not congruent completely. This may shed new light on the coevolution of host species and their microbiota.